Accounting Disclosure and Its Role in Attracting Foreign Investments - Ararawi, Anwer Ata (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the role of accounting disclosure in increasing investment to activate emerging financial markets, by presenting and clarifying the theoretical framework of accounting disclosure in emerging financial markets. In addition to evaluating the role of accounting disclosure in raising the efficiency of emerging stock markets by studying the requirements of what investors need in accordance with the requirements of presentation and disclosure in international accounting standards and closely related agreements. For this purpose, the researcher used two approaches, the first is the inductive approach through desk studies and the extrapolation of books, articles and other sources that dealt with accounting disclosure and emerging financial markets, and the second is the deductive approach by reaching the relationship between accounting disclosure and increasing the efficiency of emerging financial markets to study a number of hypotheses, the most important of which are the relationship of accounting disclosure and its role in attracting foreign investments, and the relationship of accounting disclosure and its role in achieving the dimensions of sustainable development. Major findings of this study showed that accounting disclosure helps bring foreign investments to account to achieve sustainable development in its dimensions. It also helped Jordanian investment companies reduce the degree of risk when making investment decisions to achieve sustainable economic development. It also contributed to improving the performance of investment companies in a way that helps achieve the electronic dimension and helped investment companies and investors to develop their financial operations to avoid high investment risks. Based on these results, the researcher recommended the need for all companies' departments to rely on accounting disclosure and its tools because of its role in attracting foreign investments, paying attention to electronic accounting disclosure because of its role in the ease of obtaining information to help in decision-making, achieving development and reducing the degree of risk when making investment decisions.
Keywords: Accounting disclosure; foreign investments; Emerging capital markets; Stock markets; international accounting standards; Investment companies